A Fluid Model for Systems with Random Disruptions - Chen, Hong; Yao, David D. (Operations Research, 1992)
Motivated by modeling manufacturing systems in which job arrivals and processing times are essentially deterministic, but the environment is typically random, we develop a fluid model with random disruptions. The quality and relevance of such a model are supported by the following facts which we establish in this study. The fluid model is more susceptible to analysis: Its (dynamical) sample paths are continuous and piecewise linear, and its stationary behavior can be studied using standard approaches in random walk; the model is a limit of corresponding queueing systems with random disruptions that are usually difficult to analyze; there exist pathwise bounds between the fluid model and D/D/1 queues with random disruptions, and the bounds are simple and tight.